More Than Nature: Why Do Tourists Return to Ecotourism? Exploring the Dimensions of Memorable Tourist Experiences as a Determinant of Revisit and Recommend Intention - Amir, Sjafril; Astuti, Widji; Chandrarin, Grahita (Journal of Ecohumanism, 2024)
This study aims to identify the dimensions of memorable tourist experiences (MTEs) that influence the intention to revisit (IRev) or recommend (IRec) ecotourism destinations in Indonesia. The dimensions analyzed were hedonism (HDN), novelty (NOV), involvement (INV), local culture (LCC), refreshment (REF), meaningfulness (MEA), and knowledge (KNW). Data were collected through questionnaires from 400 tourists visiting three national parks in Indonesia. Results showed that INV, NOV, and MEA significantly affected revisit and recommendation intentions, while HDN and KNW had no significant effects. Furthermore, LCC and REF only influenced revisit intention. These results suggest that MTEsin ecotourism focus on INV, NOV, and MEA values. This study contributes to the tourism literature and guides destination managers to enhance tourists’ revisit intentions.